COMPARATIVE STUDY OF SOCIAL SKILLS COLLEGE STUDENTS OF THE FACULTY OF MATHEMATICS USING MULTIVARIATE METHOD - Kuroiwa Quispe, Oscar (2013)
In the present research make a comparison of academic social skills on students enrolled in the Faculty of Mathematics (FCM) at the National University of San Marcos by sex, using the measuring instrument of Social Skills Scale Goldstein and multivariate methods, including Hotelling T2 statistic. and factor analysis (Johnson and Wichern, 1992), to analyze the data collected. In the sample design, stratified random sampling (Scheffer and Mendenhall, 2007) with proportional allocation to size in each stratum considered as strata to Professional Academics Schools (E.A.P.) of Faculty of Mathematics Sciences. To calculate the sample size used stratified random sampling with a limit for the estimation error of 2,2 and and the information provided by the Academic Board of the Faculty of Mathematics, of students enrolled the second semester of academic year 2009, the sample size was 301 students, divided in proportion to the four Professional Academics Schools of the Faculty of Mathematics.